HOTS-Based Learning Methodology Innovation in Islamic Religious Education: A Case Study at State Senior High School 1 Karanganyar - Nashir, Muhammad Jafar; Wardani, Anita; Intan Apriliani, Elina; Zahiri, Muhammad (Jurnal Tarbiyatuna, 2025)
The development of Higher Order Thinking Skills (HOTS) has become a key priority in contemporary Islamic Religious Education (IRE) to foster students”™ critical, analytical, and reflective thinking. This study aims to examine the innovation of HOTS-based learning methodologies in Islamic Religious Education at State Senior High School 1 Karanganyar. Employing a qualitative case study approach, data were collected through classroom observations, in-depth interviews with teachers and school leaders, and document analysis of lesson plans and instructional materials. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that HOTS-based learning in IRE is implemented through problem-based learning, contextual learning activities, open-ended questioning, and reflective discussions that actively engage students in higher-level cognitive processes. However, the implementation faces several challenges, including teachers limited pedagogical competence in HOTS-oriented instruction, constraints in learning time allocation, and students varied academic readiness. Despite these challenges, HOTS-based methodology innovation contributes positively to improving students”™ critical thinking, learning engagement, and conceptual understanding in Islamic Religious Education. This study highlights the importance of continuous professional development and institutional support in strengthening HOTS-based pedagogical practices in secondary Islamic education.